Persepsi Anggota Grup Facebook “Komunitas Hidroponik Jogja (Hi-Jo)” Terhadap Pengembangan Hidroponik - Aulifia Aulifia; Subejo Subejo; Harsoyo Harsoyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
Research was conducted on theFacebook group Jogja Hydroponic Community, in order to know: 1) Characteristics of the Hi-Jo Community Facebook group members, 2) Level of perception of the Hi-Jo Community Facebook group members towards hydroponic development, and 3) Factors which affect the perception of the Hi-Jo Community Facebook group members towards hydroponic development. The method used in this research was descriptive method with survey techniques. Sampling was undertaken purposively on Facebook group, with random respondents. From the total sample of 7634 members, has been taken 52 people from Hi-Jo Community Facebook group. The analytical method used was the proportion test and multiple linear regression analysis. The research results showed that the characteristics of the Hi-Jo Community Facebook group members was balanced between men and women, the majority of main occupation was student, the majority of secondary occupation was student. The perception level of the Hi-Jo Community Facebook group members was categorized as high. Activeness, experience, and the role of the admin gave a positive effect to perception, whereas age, education and use of the products did not significantly affect the perception.